Applications of water-stable metal-organic frameworks in the removal of water pollutants: A review. (15th December 2021) - Zhang, Shu; Wang, Jiaqi; Zhang, Yue; Ma, Junzhou; Huang, Lintianyang; Yu, Shujun; Chen, Lan; Song, Gang; Qiu, Muqing; Wang, Xiangxue
Abstract: Because the pollutants produced by human activities have destroyed the ecological balance of natural water environment, and caused severe impact on human life safety and environmental security. Hence the task of water environment restoration is imminent. Metal-organic frameworks (MOFs), structured from organic ligands and inorganic metal ions, are notable for their outstanding crystallinity, diverse structures, large surface areas, adsorption performance, and excellent component tunability. The water stability of MOFs is a key requisite for their possible actual applications in separation, catalysis, adsorption, and other water environment remediation areas because it is necessary to safeguard the integrity of the material structure during utilization. In this article, we comprehensively review state-of-the-art research progress on the promising potential of MOFs as excellent nanomaterials to remove contaminants from the water environment. Firstly, the fundamental characteristics and preparation methods of several typical water-stable MOFs include UiO, MIL, and ZIF are introduced. Then, the removal property and mechanism of heavy metal ions, radionuclide contaminants, drugs, and organic dyes by different MOFs were compared. Finally, the application prospect of MOFs in pollutant remediation prospected. In this review, the synthesis methods and application in water pollutant removal are explored, which provide ways toward the effective use of water-stable MOFs in materials design and environmental remediation. Graphical abstract: Image 1 Highlights: The synthesis strategies of water-stable MOFs are briefly introduced. The mechanisms mainly ascribe to coordination and electrostatic interaction. Sufficient functional groups endow MOFs excellent performance. Multi-factor influences demonstrate the practical application potential of MOFs.